Peritoneal dialysis-associated peritonitis: incidence, microbiology and outcomes at a South African hospital - Lang, Ian; Ensor, Jason; Freercks, Robert (African Journal of Nephrology, 2026)
Background: Kidney failure is a major health issue in South Africa. The public health sector has adopted a ‘peritoneal dialysis (PD) first’ policy for kidney replacement therapy. PD may be characterized by high failure rates, commonly due to PD-associated peritonitis (PDP), although no data exist for the Eastern Cape (EC) province. Here we describe PDP episodes and their outcomes at a tertiary hospital in Gqeberha, EC. Methods: A retrospective study was conducted on all adult patients receiving chronic PD at Livingstone Tertiary Hospital from 2022–2024, evaluating microbiological profiles and outcomes of all PDP episodes. Results: Of 91 patients (mean age 38.8 years; 52% male), 61 (67%) experienced PDP. Overall, 117 episodes of PDP occurred over 126.9 patient-years (0.85 episodes/patient-year). Twelve patients (20%) had ≥3 episodes. The culture negative rate was low (11%); Gram-positive organisms predominated (71%). The medical cure rate was 65%. Relapse (OR 0.21; 95% CI 0.06–0.76) and fungal episodes (OR 0.09; CI 0.02–0.39) were associated with lower odds of cure, whereas Gram-positive cases had higher odds than Gram-negatives (OR 3.19; 1.18–8.64). HIV was not associated with episode profile or outcomes. Catheter removal occurred in 21 (18%) episodes; 16 (14%) episodes required modality switch to haemodialysis. Only four patients successfully resumed PD after interval haemodialysis. Conclusions: PDP rates in EC exceed international targets and contribute to technique failure. Culture-negative and medical cure rates were acceptable. Gram-positive organisms predominated, suggesting a need for improved patient training. Resource restrictions and socio-economic factors may contribute to the high rate.